Relations between income inequality, economic growth and poverty threshold: new evidences from EU countries panels - Soava, Georgeta; Mehedintu, Anca; Sterpu, Mihaela (Technological and Economic Development of Economy, 2020)
This paper analyses the relationship between the following indicators: income inequality, gross domestic product, risk of poverty threshold and median equivalized net income for a panel of 28 countries of European Union (EU) over the period 2005-2016. Two theoretical regression models, a linear and a quadratic one, are used to estimate the influence on income inequality of the other three indicators. Empirical estimations, using panel data techniques on three different data panels, confirm the Kuznets hypothesis that income inequality tends to increase with early economic development and tends to decrease when a country reaches a certain level of development. We found that for emerging EU countries, income inequality has a growing tendency with a positive economic growth and maybe reduced by increasing risk of poverty threshold or median equivalized net income. For highly developed EU countries the situation is completely opposite. At EU level, the influence of gross domestic product on income inequality is strongly determined by its trend in the highly developed EU countries, while the influence of risk of poverty threshold and median equivalized net income on income inequality is strongly determined by their trend in the emerging EU countries.First published online 19 November 2019